Factores demográficos clínicos y rango de movilidad en fractura supracondílea humeral tratado quirúrgicamente con clavos cruzados años 2019-2022 en niños menores de 12 años Hospital Regional de Loreto - Pinchi Torres, Jharley di Stilger (2025)
The objective of the research was to determine the relationship between demographic and clinical factors and range of mobility, in 88 patients under 12 years of age, with humeral supracondylar fracture treated surgically with crossed nails between 2019-2022 in a public hospital in Iquitos. Regarding the research methodology, it is quantitative, descriptive, correlational, non experimental, transversal, retrospective in design; The instrument Recording sheet on clinical factors and treatment of humeral supracondylar fracture in children was used to obtain data from the clinical history. The results were: of the 45.5% who had a good range of mobility, 31.85% excellent and 22.7% fair ;56.8% were between 3 and 6 years old, followed by 30.7% between 7 and 12 years old, 63.6% were male, 67.0% lived in an urban area, 94.3% had an extension type of fracture according to the mechanism, and 73.8% had a type III fracture according to the Gartland classification. Finding statistical significance between the good range of mobility with age (p=0.002) and with type fracture according to the Gartland classification (p=0.024); and absence of statistical significance between good range of mobility with sex (p=0.927), with area of residence (p=0.581), and extension fracture (p=0.243). The study concludes that surgical treatment with crossed nails provides a greater range of mobility according to Flynn's criteria in the children studied.